Self-hydration and thermoregulatory processes of average-level paddlers during international surfski events in a tropical climate - O Hue; P Le Ieannic; K Chamari (Termedia Publishing House, 2016)
The aim was to investigate thermal response, hydration behaviour and performance in flatwater kayaking races in tropical conditions (35.9 1 28°C and 64 1 4% RH). Eight regionally ranked paddlers (ARP) participated in the 2012 Surfski Ocean Racing World Cup in Guadeloupe (an inline 15-km downwind race). Core temperature (TC) and heart rate (HR) were measured using portable telemetry units, while water intake was deduced from backpack absorption. The kayakers were asked to rate both their comfon sensation and thermal sensation on a scale before and after the race. The performance was not related to any measured parameters, and high values of post-race TC were related to high pre-race TE. The present study demonstrated that average- range paddlers are able to perform in a tropical climate, drinking little and paddling at high intensity without any interference from thermal sensations. Core temperature at the end of the race was positively related to pre- race To which reinforces the importance of beginning surfski races with a low T; and raises the question of pre- cooling strategies for paddlers, and more specifically for those with a low convection body surface.